Pencatatan dan Pelaporan Vaksinasi COVID-19 dengan Aplikasi PCare Vaksinasi di Puskesmas Seputih Banyak - Azizatul Azza; Mieke Nurmalasari (Indonesian Journal Publisher, 2022)
COVID-19 has spread throughout the world, so it has a pandemic status. One of the countries infected with the COVID-19 pandemic is Indonesia. The Indonesian government's efforts to stop the spread of COVID-19 are through the COVID-19 vaccination. Every health service facility that carries out the COVID-19 vaccination must record and report the results of the COVID-19 vaccination service through the Vaccination PCare application. The obstacles found at the Seputih Banyak Health Center were data that numbered in the thousands so that the officers were overwhelmed when entering data. This study aims to determine the implementation of recording and reporting of COVID-19 vaccination using the Vaccination PCare application. Data collection in this study was carried out by observing the input, process, and output of the recording and reporting of COVID-19 vaccination using the Vaccination PCare application. . The data analysis used descriptive analysis. The results showed that during the recording and reporting of COVID-19 vaccination, regulations, human resources, process and output were by the provisions, while the facilities are not entirely appropriate. Facilities that are not appropriate are the unavailability of wifi and printers.